Lethocolea Mitt. (Acrobolbaceae, Marchantiophyta) new to China with special reference to its first plastome - Xu, Jonathan; Zhao, Yi-Di; Yin, Deng-Pan; Xu, Hao; Zhu, Rui-Liang (Phytotaxa, 2025)
Lethocolea (Acrobolbaceae, Marchantiophyta) is a small liverwort genus with four currently accepted species and one doubtful species (Lethocolea indica). Despite a recent taxonomic revision, L. indica, a poorly understood species known only from northern India, remains doubtful and requires further examination. This study reports the first occurrence of Lethocolea in China, where L. indica was found in the Black-necked Crane Provincial Nature Reserve in Yunnan. We present the first complete plastome of Lethocolea, which is 119,056 bp in length and contains 130 functional genes. Phylogenetic analyses based on the rps4 gene indicate that L. indica belongs to the subgenus Lethocolea and is closely related to L. javanica, which is known from Australia, Indonesia (Java), New Caledonia, New Zealand, and southern India. The present study provides a detailed description and illustration of L. indica, highlighting its morphological resemblance to L. javanica. We propose further investigation into the taxonomic status of L. indica, including additional population sampling and expanded molecular-phylogenetic analyses with more molecular markers.